THE ROLE OF VILLAGE GOVERNMENT IN MANAGING CORPORATE SOCIAL RESPONSIBILITY OF PT. INDONESIA HUABAO INDUSTRIAL PARK (IHIP) IN AMBUNU VILLAGE, BUNGKU BARAT DISTRICT, MOROWALI REGENCY - Nanang Nardiyanti Rusdin; Muh Nawawi; Muhammad Arief (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The purpose of this study is to determine and evaluate the role of the village government in managing Corporate Social Responsibility in Ambunu Village, West Bungku District, Morowali Regency. This study uses Ryaas Rasyid's theory with 4 aspects, namely: Facilitator, Regulator, Dynamist, and Catalyst. Researchers use qualitative research methods with a descriptive approach. Data collection techniques are carried out by observation, interviews, and documentation. Informants in this study amounted to 6 people, namely the Village Head, BPD, PT. IHIP, and 3 community members. Based on the results of field research and interviews with various informants, it shows that the Ambunu village government has carried out its role as a facilitator by facilitating dialogue between the community and the company. However, there are still shortcomings in the dissemination of information and the fulfillment of infrastructure needs. As a regulator, the role of the village government has not been optimal due to the lack of specific regulations governing the supervision and accountability of CSR fund management. As a dynamic agent, the village government is active in planning and implementing CSR programs, encouraging innovation, and ensuring that community needs are met, although there are still challenges in equitable fulfillment of needs and increasing community participation. As a catalyst, the village government has attempted to facilitate community participation and implement aligned programs. However, improvements in outreach and information delivery are needed to achieve the desired impact. This research includes improving the quality of outreach, optimizing program implementation, strengthening partnerships, increasing community participation, and enhancing transparency and accountability in CSR management.